2008
DOI: 10.1007/s10103-008-0631-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a specially pulsed electric field on an animal model of wound healing

Abstract: The possible beneficial effects of a specially pulsed electric field (PEF) on wound healing were investigated in this study. We made a pair of triangular, full-thickness, dorsal incisions in the skin of 32 healthy male mice (one control group and three exposure groups). The treatment groups were kept between parallel plates in a partially insulated exposed environment. Group I was exposed to an electric field intensity of 10 kV/m, group II was exposed to 1.9 kV/m, and group III was exposed to 0.9 kV/m. PEFs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
3
8
0
Order By: Relevance
“…In light of this, our study demonstrated for the first time that ES-exposed skin fibroblasts were able to reduce the size of a 3D collagen matrix. These findings concur with those of an animal study showing that direct current EF favorably affected collagen synthesis and wound closure/contraction [62]. Wound contraction is predominantly myofibroblast-dependent [63].…”
Section: Discussionsupporting
confidence: 91%
“…In light of this, our study demonstrated for the first time that ES-exposed skin fibroblasts were able to reduce the size of a 3D collagen matrix. These findings concur with those of an animal study showing that direct current EF favorably affected collagen synthesis and wound closure/contraction [62]. Wound contraction is predominantly myofibroblast-dependent [63].…”
Section: Discussionsupporting
confidence: 91%
“…Formation and deposition of collagen fibers are particularly important for wound repair because collagen is necessary for granulation tissue organization and tissue membrane regeneration during the wound healing process [ 23 ]. Additionally, more collagen observed in Group SC showed that electrical stimulation generated by the OPP may have affected collagen synthesis by the fibroblasts, as observed in previous study [ 24 ]. These results suggest that OPP-derived electrical stimulation treatment can expedite collagen synthesis in the wound lesion and better regenerate the basal and epidermis layer to reduce the wound defect area.…”
Section: Discussionsupporting
confidence: 79%
“…The pyroelectric and piezoelectric nature of the epidermal layer of skin may help to find novel ways to manipulate skin tissue adaptation and remodeling (Athenstaedt et al 1982 ). Guided cell movement and migration can be achieved by applying small electric fields, and consequently can improve in vivo skin healing (Cinar et al 2009 ). Such studies demonstrated that exposure of wounds with0.9 kV/m to 1.9 kV/m chopped direct current (DC) electric field with a 30 micros repetition time favourably affected collagen synthesis and subsequent wound recovery.…”
Section: Role Of Microenvironment In Skin Regenerationmentioning
confidence: 99%